Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1017/s0021859600069951
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and calcium metabolism in growing calves with special emphasis on phosphorus homoeostasis. 4. Studies on milk-fed calves given different amounts of dietary phosphorus but a constant intake of calcium

Abstract: SUMMARYFriesian bull calves, 2 weeks old, were given an experimental diet of cow's milk supplemented with phosphorus to provide three rates of P intake: adequate, high, and very high. After 1 week's preliminary feeding, studies of absorption, endogenous secretion, urinary excretion, serum concentration, retention and kinetics of Ca and P metabolism were made by a balance and dualradioisotope technique with 32P and 45Ca.The efficiency of P absorption decreased significantly as the P intake increased and the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Relationship between the ratio of faecal endogenous phosphorus to total faecal phosphorus (PFEC ENDO / PFEC TOT ) and urinary phosphorus (PURI, g·kg [18] as illustrated in model 16 and Figure 3. We found urinary phosphorus flow non significant when dietary supply was low but significant above a step of requirements [7,19], and correlated (r 2 = 0.53) with ingested phosphorus (model 17, Fig. 4).…”
Section: Urinary Phosphorus Excretionmentioning
confidence: 82%
See 3 more Smart Citations
“…Relationship between the ratio of faecal endogenous phosphorus to total faecal phosphorus (PFEC ENDO / PFEC TOT ) and urinary phosphorus (PURI, g·kg [18] as illustrated in model 16 and Figure 3. We found urinary phosphorus flow non significant when dietary supply was low but significant above a step of requirements [7,19], and correlated (r 2 = 0.53) with ingested phosphorus (model 17, Fig. 4).…”
Section: Urinary Phosphorus Excretionmentioning
confidence: 82%
“…This ratio of endogenous faecal phosphorus to total faecal phosphorus is highly variable from 0.12 to 0.95 in our database. The lowest value (0.12) was obtained in a growing calf fed a milk-based diet [7] and in adult sheep fed a diet rich in wheat bran [21]. The highest value (0.95) was obtained with high forage content diets as in the study of [22] for the determination of phosphorus availability in alfalfa hay.…”
Section: Faeces the Main Phosphorus Excretion Routementioning
confidence: 95%
See 2 more Smart Citations
“…The RC of Ca obtained in this study was 73.18% (Table 3); this is higher than that of BR-CORTE (2016), which was reported as 56.8% for Zebu beef cattle. Challa and Braithwaite (1989) reported an RC for Ca of 83% for 138-kg calves, and Yuangklang et al (2004) reported an absorption coefficient for Ca of 95% for 47kg calves. NRC (2001) and AFRC (1991) recommended values of 70 and 68%, respectively, as absorption coefficients for Ca.…”
Section: Camentioning
confidence: 99%